Traversing the cascade: urgent research priorities for implementing the 'treat all' strategy for children and adolescents living with HIV in sub-Saharan Africa - Leslie A. Enane; Mary-Ann Davies; Valériane Leroy; Andrew Edmonds; Edith Apondi; Adebola Adedimeji; Rachel C. Vreeman (Elsevier, 2018)
Children and adolescents living with HIV (CALHIV) in sub-Saharan Africa experience significant morbidity and alarmingly high mortality rates due to critical gaps in the HIV care cascade, including late diagnosis and initiation of treatment, as well as poor retention in care and adherence to treatment. Interventions to strengthen the adult HIV care cascade may not be as effective in improving the cascade for CALHIV, for whom specific strategies are needed. Particular attention needs to be paid to the contexts of sub-Saharan Africa, where more than 85% of the world's CALHIV live. Implementing the 'treat all' strategy in sub-Saharan Africa requires dedicated efforts to address the unique diagnosis and care needs of CALHIV, in order to improve paediatric and adolescent outcomes, prevent viral resistance and reduce the number of new HIV infections. We consider the UNAIDS 90-90-90 targets from the perspective of infants, children and adolescents, and discuss the key challenges, knowledge gaps and urgent research priorities for CALHIV in implementation of the 'treat all' strategy in sub-Saharan Africa.